A new species of Phanera (Leguminosae: Cercidoideae) from the Western Ghats of Kerala, India - Vadhyar, Rakesh G.; Benjamin, J. H. Franklin (Phytotaxa, 2019)
A new species of Phanera from southern Western Ghats, India, is described as P. murthyi. It appears to be endemic to Kozhikode district, Kerala.